EP2 Receptor Activates Dual G Protein Signaling Pathways that Mediate Contrasting Proinflammatory and Relaxatory Responses in Term Pregnant Human Myometrium - Kandola,MK; Sykes,L; Lee,YS; Johnson,MR; Hanyaloglu,AC; Bennett,PR (Endocrinology, 2013)
Prostaglandin (PG) E2 (PGE2) plays a central role in the regulation of smooth muscle contractions. Classically, PGE2 stimulates contractions via EP1 and EP3 receptors, whereas EP2 and EP4 maintain quiescence. Labor involves a change from myometrial quiescence to contractions with a shift from anti- to proinflammatory pathways. EP2, a Gαs-coupled receptor, is known to mediate its actions via cAMP signaling. However, we have recently shown that EP2 also activates the proinflammatory PG G/H synthase-2 (PGHS-2). Here, we identify the mechanism underlying the ability of EP2 to maintain uterine quiescence and activate a proinflammatory/prolabor response in term-pregnant human myometrium. Human myometrial biopsies for in vivo and in vitro studies were taken at cesarean section at term, before or after the onset of labor. Activation of EP2 increased intracellular levels of cAMP and reduced contractility. Contrastingly, EP2 stimulation increased levels of PGHS-2, PG synthase mPGES-1, and PGE2. This was entirely dependent on EP2-mediated activation of calcium signaling. Both calcium signaling and up-regulation of PGHS-2 were insensitive to the Gαi inhibitor pertussis toxin but inhibited by siRNA knockdown of Gαq/11. There were no differences in EP2 mRNA or protein levels between upper or lower segment myometrium or between pre- and postlabor myometrium. However, in myocytes taken after the onset of labor, cAMP signaling was markedly attenuated, whereas activation of calcium and PGHS-2 was preserved. Overall, the dual coupling of EP2 to Gαs-cAMP and Gαq/11-calcium pathways underlies its ability to mediate contrasting functions in term pregnancy and the “switching” to a prolabor receptor.